1996
DOI: 10.1083/jcb.133.3.559
|View full text |Cite
|
Sign up to set email alerts
|

Membrane fusion mediated by the influenza virus hemagglutinin requires the concerted action of at least three hemagglutinin trimers.

Abstract: Abstract. In this study we tested the hypothesis that fusion mediated by the influenza virus hemagglutinin (HA) is a cooperative event. To do this we characterized 3T3 cell lines that express HA at nine different defined surface densities. HA densities ranged from 1.0 to 12.6 × 103 HA trimers/~m 2 as determined by quantitative fluorescent antibody binding. The lateral mobility and percent mobile fraction of HA did not vary significantly among these cells, nor did the contact area between HA-expressing cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
338
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(382 citation statements)
references
References 69 publications
41
338
2
Order By: Relevance
“…It may represent the time required to form a fusion pore and deliver the luciferase into the cell cytoplasm and then access its substrates. Indeed, the data are consistent with the relatively slow formation of the fusion pore seen for other enveloped viruses such as influenza A virus and VSV, which can take many minutes to grow large enough to release the virus capsid (8,21). However, the lag may also indicate that cellular signaling, reorganization, or trafficking events may be required for entry, as suggested for HIV (13).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…It may represent the time required to form a fusion pore and deliver the luciferase into the cell cytoplasm and then access its substrates. Indeed, the data are consistent with the relatively slow formation of the fusion pore seen for other enveloped viruses such as influenza A virus and VSV, which can take many minutes to grow large enough to release the virus capsid (8,21). However, the lag may also indicate that cellular signaling, reorganization, or trafficking events may be required for entry, as suggested for HIV (13).…”
supporting
confidence: 74%
“…This is principally because, for these viruses, it is possible to induce an en masse fusion event by dropping the pH of the medium. Under these circumstances, fluorescence dequenching, or FRET (fluorescence resonance energy transfer), assays effectively measure the kinetics of fusion and have been used to understand the effects of mutations and antiviral drugs (3,8). For this, fluorescent probes incorporated into the virus membrane mix with and become diluted into the target cell or liposome membrane.…”
mentioning
confidence: 99%
“…Furthermore, using polypeptide cross-linking agents and sulfhydryl group reagents, Markovic et al (1998) demonstrated that GP64 forms transient, higher-order complexes of trimers upon application of low pH buffer (only in the presence of target membrane) at the same time that fusion is catalyzed. The ring hypothesis is further supported by work with influenza HA, which suggests that HA trimers function cooperatively and inhibit lipid dye transmigration during the initial fusion phases (Ellens et al, 1990;Clague et al, 1991;Tse et al, 1993;Zimmerberg et al, 1994;Blumenthal et al, 1996;Danieli et al, 1996;Chernomordik et al, 1998).…”
Section: The Mechanism Of Membrane Fusionmentioning
confidence: 59%
“…A working model for the process of SARS CoV virion/ cell fusion can be extrapolated from this work and from work in several other RNA virus systems (10,22,24,29,42,46,82). After the fusion protein binds to the cellular receptor, the fusion protein undergoes a series of rearrangements, including the release of the receptor-binding subunit (S1) and trimerization and extension of the N helices of the S2 subunit toward the target membrane.…”
Section: Discussionmentioning
confidence: 99%